Occupational lifting is associated with hip osteoarthritis: a Japanese case-control study. - Yoshimura, N; Sasaki, S; Iwasaki, K; Danjoh, S; Kinoshita, H; Yasuda, T; Tamaki, T; Hashimoto, T; Kellingray, S; Croft, P; Coggon, D; Cooper, C (2000)
OBJECTIVE: Hip osteoarthritis (OA) is a frequent cause of pain and disability in Western countries, but the disorder is less common in Japan. A case-control study in Britain found obesity, hip injury, and occupational lifting to be associated with hip OA among men and women. However, there are few epidemiological studies concerning factors associated with hip OA in Japan. We performed a comparable case-control study of the disorder in Japan, and contrasted the findings with those from Britain. METHODS: The study was carried out in 2 health districts in Wakayama Prefecture, Japan. Cases were men and women aged > or = 45 years listed for total hip arthroplasty due to OA over one year, and who did not have an established cause of secondary OA (e.g., rheumatoid arthritis, ankylosing spondylitis). For each case, a control was selected randomly from the general population and was individually matched to the case for age, sex, and district of residence. Cases and controls were interviewed with a structured questionnaire about medical history, physical activity, socioeconomic factors, and occupation. Measurements were made of height and weight. RESULTS: One hundred fourteen cases (103 women, 11 men) were compared with 114 controls. We found no relationship between obesity and hip OA (OR = 1.0, 95% CI 0.5-1.9; highest vs lowest thirds of distribution of body mass index). There was, however, a statistically significant association between occupational lifting and hip OA, such that regular lifting of 25 kg in the individual's first job (OR = 3.6, 95% CI 1.3-9.7) or of 50 kg in their main job (OR = 4.0, 95% CI 1.1-14.2) was associated with increased risk of hip OA. These associations remained after adjustment for potential confounding variables. In contrast, those subjects who spent > 2 h each day sitting during their first job were significantly less likely to have the disorder (crude OR = 0.5, 95% CI 0.3-0.9). This association also remained statistically significant after adjustment for potential risk factors. CONCLUSION: Our findings support the hypothesis that occupational physical activity, particularly the lifting of very heavy loads in the workplace at regular intervals, predisposes to hip OA in both Britain and Japan. The lack of association between obesity or hand involvement and hip OA in Japan suggests that the contribution of constitutional and mechanical risk factors to this disorder might differ in different populations. However, attention to manual handling in the workplace would appear an important aspect of preventive strategies against hip OA in Western and Oriental populations.